2005
DOI: 10.1089/sur.2005.6.397
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model of Invasive Aspergillosis: Variable Benefit of Interferon-Gamma Administration under In Vitro and In Vivo Conditions

Abstract: The in vitro and in vivo effects of IFN-gamma in IA are contingent on many variables, including the route of administration and the specific pathogenesis of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The finding of a sensitizing role for exogenous IFN, while surprising, has been described in other infectious models. Exogenous IFN−γ, while improving phagocytosis in vitro and in vivo , increases mortality in a murine model of invasive aspergillosis [20]. Similar results have been observed in a murine model of invasive candidiasis [21].…”
Section: Discussionsupporting
confidence: 70%
“…The finding of a sensitizing role for exogenous IFN, while surprising, has been described in other infectious models. Exogenous IFN−γ, while improving phagocytosis in vitro and in vivo , increases mortality in a murine model of invasive aspergillosis [20]. Similar results have been observed in a murine model of invasive candidiasis [21].…”
Section: Discussionsupporting
confidence: 70%
“…In vivo, systemic IFN-g did not improve phagocytosis or killing by neutrophils or affect mortality. Local nasal IFN-g enhanced phagocytic recruitment to the lungs but worsened mortality (34). IFN-g has also been used as adjunctive therapy to standard antifungal treatment in humans and improved outcomes (35).…”
Section: Discussionmentioning
confidence: 99%
“…After the initial proinflammatory response to A. fumigatus associated with TLRs, phagocytes use both oxidative and nonoxidative mechanisms in concert to damage the hyphae of A. fumigatus (9,29). While a number of cytokines upregulate these antifungal phagocytic activities (12,14,16), antifungal agents may assist in further damaging hyphae. Sau et al found that amphotericin B induces signal transduction and inflammatory cytokine release from cells expressing TLR2, and the adapter protein MyD88 responds to amphotericin B with NF-B-dependent reporter activity and cytokine release (28a).…”
Section: Discussionmentioning
confidence: 99%